105k views
1 vote
Solve this equation. (3x+10)−(2x−9)=43

2 Answers

5 votes

Answer:

x = 24

Explanation:

Simplify

( 3 x +10 ) − ( 2 x − 9 )

Simplify each term.

Apply the distributive property.

3 x + 10 − ( 2 x)− = 43

Multiply 2 by − 1 .

3 x + 10 − 2 x − − 9 = 43

Multiply − 1 by − 9 .

3 x + 10 − 2 x + 9 = 43

Simplify by adding terms.

Subtract 2 x from 3 x .

x + 10 + 9 = 43

Add 10 and 9 .

x + 19 = 43

Move all terms not containing x to the right side of the equation.

Subtract 19 from both sides of the equation.

x = 43 − 19

Subtract 19 from 43 .

x = 24

User Markau
by
5.2k points
5 votes

Answer: X = 24

Explanation:

Move all terms to the left:

(3x + 10) - (2x - 9) - 43 = 0

Get rid of all the parenthesis:

3x + 10 - 2x - 9 - 43 = 0

Add all the numbers and all variable:

x-24 = 0

Move all terms containing x to the left and all other terms to the right:

x = 24

User Nima Soltan
by
4.8k points